Pengaruh Permainan Edukatif Media Flashcard Terhadap Kemampuan Bahasa Inggris Anak Usia 3-6 Tahun di Kecamatan Ujung Pandang Kota Makassar - Anaya Atrida, Hatirah; Latif, M. Ali; Nur Alamsyah, Muhammad; Arsyad, Yolandika; Fahmi, Rahmat (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study aims to determine whether or not there is an influence of flashcard media educational games on the English skills of children aged 3-6 years in Ujung Pandang District. This research uses a quantitative approach with a type of experimental research. The subjects of this study were educators and children aged 3-6 years. While the object of this study is TK – Baby House or PAUD. Data collection using observation, interview, pre-test and post-test methods. The technique used in data analysis using re-experiment design (pretest – posttest control group design) is that if there is a difference between pretest and posttest scores, where the posttest score is significantly higher than the pretest score, it can be concluded that the treatment given has an influence or is effective on changes that occur in the dependent variable. Based on the results of the study shows that there is a significant relationship between flashcard media educational games on the English skills of children aged 3-6 years in Ujung Pandang district